Evaluating CRP and Procalcitonin in Pediatric Sepsis: Diagnostic Markers with Surgical Implications - Hamza Sohail, Farhat Altaf, Tabassum Bashir, Tahir Shahzad Nawaz Babar,Abid Ali Ranjha, Muhammad Ahmad Raza Butt, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pediatric sepsis is a critical condition with significant morbidity and mortality, especially whenearly diagnosis is delayed. This prospective analytical study investigates the diagnostic utility ofC-reactive protein (CRP) and procalcitonin (PCT) in differentiating sepsis severity and predictingsurgical outcomes in pediatric patients